Vibration failure and anti-vibration analysis of an annular-grooved PDC bit. (September 2020) - Huang, Kuilin; Yang, Yingxin; Liu, Yang; Niu, Qingzhi
Highlights: The cause of the vibration failure of the bit and transverse bit motion are analyzed. Designs and manufactures annular-grooved experimental bit with variable parameters. The developed annular-grooved PDC bit can reduce bit vibration and improve bit's drilling stability. Abstract: To extend the service life of drill bits through reducing various drilling vibrations, this paper presents a fundamental analysis of the root cause of failure for polycrystalline diamond compact (PDC) bits during the drill-based process of vortex generation. In this work we develop a new type of PDC drill bit, namely the annular-grooved PDC bit, which can form one or more annular convex rock ridges at the bottom of the hole, having a raised ring that can limit transverse vibration. Our experimental results confirm that the accelerations of the annular-grooved PDC bit in axial, tangential, and radial directions are smaller than that of a conventional PDC bit. More specifically, acceleration declines by 33.5%, 21.6%, and 25.9% in tangential, axial, and radial direction, respectively. Our experimental investigation also shows that, as the weight on bit and the rotation speed increase, bit vibration intensifies, and the impact load on bit increases which can worsen bit stability. However, as the height and the width of the rock ridge increase, the drilling vibrations in three directions can decline. Therefore, the developed annular-grooved PDC bit can reduce bit vibration and improve bit's drilling stability.